Hazardous forecasts and crisis scenario generator - e uthor; e uthor (London : ISTE Press Ltd ; Kidlington, Oxford : Elsevier Inc, 2015)
This book presents a crisis scenario generator with black swans, black butterflies and worst case scenarios. It is the most useful scenario generator that can be used to manage assets in a crisis-prone period, offering more reliable values for Value at Risk (VaR), Conditional Value at Risk (CVaR) and Tail Value at Risk (TVaR). Hazardous Forecasts and Crisis Scenario Generator questions how to manage assets when crisis probability increases, enabling you to adopt a process for using generators in order to be well prepared for handling crises.
Includes bibliographical references and index.
Vendor-supplied metadata.
Keywords: Economic forecasting; International finance -- Forecasting; Globalization -- Economic aspects; BUSINESS & ECONOMICS -- Economics -- General; BUSINESS & ECONOMICS -- Reference; Economic forecasting; Globalization -- Economic aspects; International finance -- Forecasting; Electronic books